GAMBARAN KECEMASAN, DEPRESI DAN MEKANISME KOPING PERAWAT MENGHADAPI MASA PANDEMI COVID-19 - TUNIK TUNIK; ELOK YULIDANINGSIH; AWAN HARIYANTO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Coronavirus disease 2019 (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and for the first time found in Wuhan, China. Nurses are one of the health professionals who are very risky to the impact of Covid-19. Anxiety psychological disorder is very commonly experienced by the nurses with various cause predictors. This research aimed to provide description of anxiety, depression, and coping mechanism of nurses during Covid-19 pandemic in Trenggalek. The design of this research was cross-sectional study with the total participants of the research were 60 nurses working at dr. Soedomo Hospital and 8 Community Health Center in Trenggalek. The instrument used in this research were two types of questionnaires regarding with anxiety and depression with DASS (Depression, Anxiety, and stress Scale), and coping mechanism to face the stressors and at last the result of the research was described. The result showed that 25% of nurses experienced mild to moderate anxiety, 10% of nurses suffered from mild to moderate depression, and 13% of nurses suffered from the symptoms of mild stress. Coping mechanism applied by the nurses when they experienced the anxiety was seeking for support, doing relaxation and light exercises and praying. Maladaptive coping mechanism used by the nurses when they experienced anxiety and stress were avoiding, self-isolation, silence, crying, anger, and so forth. According to the result, it was expected that the health service provided psychology and psychological therapy to the nurses in order to prevent further complicated impact. ABSTRAKCoronavirus disease 2019 (COVID-19) adalah penyakit yang disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) dan pertama ditemukan di Wuhan, China Perawat merupakan salah satu tenaga kesehatan yang sangat rentan menerima dampak dari munculnya covid-19. Gangguan psikologis kecemasan sangat mudah dialami oleh perawat dengan berbagai sumber penyebab. Tujuan penelitian ini adalah untuk memberikan gambaran Kecemasan, Depresi dan Mekanisme Koping Perawat di Wilayah Kabupaten Trenggalek Menghadapi Masa Pandemi Covid-19. Desain penelitian ini adalah studi cross sectional. Jumlah responden dalam penelitian ini adalah 60 perawat yang bekerja di RSUD dr.Soedomo Trenggalek dan 8 Puskesmas di wilayah Kabupaten Trenggalek. Partisipan diberikan kuesioner tentang kecemasan dan depresi dengan menggunakan DASS (Depression, Anxiety and Stress Scale),dan kuesioner yang berisi tentang mekanisme koping dalam menghadapi stressor, kemudian hasil penelitian digambarkan secara deskriptif. Hasil penelitian menunjukkan bahwa 25% perawat mengalami kecemasan ringan-sedang, 10 % perawat mengalami depresi ringan-sedang dan 13% perawat mengalami gejala psikologis stress ringan. Mekanisme koping yang digunakan oleh perawat ketika mengalami kecemasan adalah mencari dukungan, melakukan relaksasi, melakukan olahragakecil dan berdoa. Mekanisme koping maladaptif yang digunakan sebagian perawat ketika mengalami kecemasan dan stress antara lain menghindar, menyendiri, menjadi pendiam, menangis, marah dan lain-lain. Berdasarkan hasil penelitian ini, diharapkan layanan kesehatan menyediakan dukungan psikologis atau terapi psikologis pada perawat agar kecemasan atau depresi perawat tidak menyebabkan dampak yang lebih berat.